Comparison of Centrifugation and Filtration Techniques for the Size Fractionation of Colloidal Material in Soil Suspensions Using Sedimentation Field-Flow Fractionation - Gimbert, Laura J; Haygarth, Philip M; Beckett, Ronald; Worsfold, Paul J (Environmental science & technology, 2005)
Sedimentation field-flow fractionation (SdFFF) with UV detection is used to systematically investigate the effect of traditional membrane filtration and centrifugation procedures on the isolation of specific size fractions from soil suspensions. Both procedures were used to isolate the nominal <0.45 and <0.2 μm fractions from a clay soil suspension. Results showed that the membrane filtration approach seriously underestimated the total mass of particulate matter present as compared to the centrifugation approach. This has serious implications for the interpretation of results for “colloidal” and “soluble” fractions from soil suspensions and other environmental matrices obtained using the standard membrane approach. The results also show that sedimentation FFF has great potential as a robust and relatively mild technology for studying size distributions in the “colloidal” range for soil suspensions and other aquatic matrices.